Soluble checkpoint molecules as predictive biomarker for disease activity and long-term outcome in SLE - Dreveton, Léa-Sophie; Spencker, Jakob Joachim; Rincon-Arevalo, Hector; Aue, Arman; Osmanodja, Bilgin; Wiedemann, Annika; Szelinski, Franziska; Krönke, Gerhard; Dörner, Thomas; Schrezenmeier, Eva; Stefanski, Ana-Luisa (Frontiers in Immunology, 2025)
BackgroundSystemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by systemic inflammation and the involvement of multiple organ systems. The disease’s heterogeneity challenges clinical assessment, highlighting the need for personalized diagnostics and therapies. Soluble immune checkpoint molecules (sICPs) have emerged as potential biomarkers for predicting disease activity in other autoimmune diseases. However, the role of sICPs in SLE has not yet been delineated. MethodsIn this study serum concentrations of soluble co-stimulatory (sCD25, sCD27, sCD40L, s4-1BB and sCD86) and co-inhibitory checkpoint molecules (sCTLA-4, sPD-1, sPD-L1, sPD-L2, sTim-3, sGal-9 and sLAG-3) were measured by bead-based assay in 235 SLE patients. sICPs were analyzed in relation to clinical data (SLEDAI, organ involvement, C3, C4, anti-dsDNA, Siglec- 1, and sustained DORIS/LLDAS remission). Analyses included Wilcoxon rank-sum tests, multivariable logistic regressions, receiver operating characteristic (ROC) analyses, cluster analyses, and correlation matrices. ResultsHigher concentrations of sCD25, sTim-3, and sGal-9 were associated with active SLE disease (SLEDAI > 4). Cluster analysis identified highest concentrations in a SLE subgroup with more severe disease (median SLEDAI 10). These molecules correlated strongly with each other and were specifically elevated in patients with renal involvement and/ or anemia, but not with APS, skin, or joint manifestations. Low sCD25 levels were associated with sustained DORIS/LLDAS remission.ConclusionThis study highlights sCD25, sTim-3, and sGal-9 as biomarkers for active SLE and renal and hematologic involvement. Low sCD25 levels were associated with achieving long-term DORIS and LLDAS remission, underscoring the potential of sCD25 as a predictive and sensitive biomarker mandating further clinical validation.